2019
DOI: 10.1002/ajoc.201900447
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidative C−H Sulfonylation of Anilines

Abstract: An electrochemical oxidative CÀ H sulfonylation of anilines without a metal catalyst and an external oxidant has been developed. Various sodium sulfinates are compatible, generating the desired products in up to 96% yield. Preliminary mechanism studies suggest that a radical crosscoupling process is involved in this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 104 publications
0
23
0
Order By: Relevance
“…Here, we can mention only a few theoretical works devoted to structural, electronic and CT properties of DPP with thiophene [35][36][37][38][39][40][41] or furan flanks. [39][40][41] As an auxiliary method, the modeling usually supports the experiment with a "standard analysis" of conjugated backbones such as ground state geometries, [42][43][44] frontier molecular orbitals, [45] optical and electronic band gaps, [46] torsion potentials, [39] and less often excited states. [40,46] For instance, Wang et al [40] have investigated a series of conjugated dyes based on DPP with different aromatic flanks using density functional theory (DFT) and timedependent-DFT to evaluate the properties and to improve the solar cell performance of the materials under study.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we can mention only a few theoretical works devoted to structural, electronic and CT properties of DPP with thiophene [35][36][37][38][39][40][41] or furan flanks. [39][40][41] As an auxiliary method, the modeling usually supports the experiment with a "standard analysis" of conjugated backbones such as ground state geometries, [42][43][44] frontier molecular orbitals, [45] optical and electronic band gaps, [46] torsion potentials, [39] and less often excited states. [40,46] For instance, Wang et al [40] have investigated a series of conjugated dyes based on DPP with different aromatic flanks using density functional theory (DFT) and timedependent-DFT to evaluate the properties and to improve the solar cell performance of the materials under study.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, similar reactions were also presented by Lei group (Scheme 44). [54] A Pd(II)-catalyzed sulfonylation of benzylamines with sodium sulfinates using a removable bidentate directing group was illustrated by Samanta group. [55] The mechanistic study showed that radical species were involved in this reaction.…”
Section: Sulfonylation With Arenesmentioning
confidence: 99%
“…This approach was applied by Li and co‐workers who reported a two‐step five‐component reaction to synthesize biaryl substituted pyranopyrazoles 116 (28%–92%) that involved combining of aryl boronic acids 114 and 4‐bromobenzaldehyde 115 followed by four‐component condensation with ethyl 3‐oxobutanoate 22 , hydrazine monohydrate 21 and propanedinitrile 23 using Pd/C as catalyst and KF·2H 2 O as base (Scheme 24). [ 95 ]…”
Section: Review Of the Literaturementioning
confidence: 99%